2016
DOI: 10.1128/jvi.01033-16
|View full text |Cite
|
Sign up to set email alerts
|

Ferrets Infected with Bundibugyo Virus or Ebola Virus Recapitulate Important Aspects of Human Filovirus Disease

Abstract: Bundibugyo virus (BDBV) is the etiological agent of a severe hemorrhagic fever in humans with a case-fatality rate ranging from 25 to 36%. Despite having been known to the scientific and medical communities for almost 1 decade, there is a dearth of studies on this pathogen due to the lack of a small animal model. Domestic ferrets are commonly used to study other RNA viruses, including members of the order Mononegavirales. To investigate whether ferrets were susceptible to filovirus infections, ferrets were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 33 publications
5
63
1
Order By: Relevance
“…However, despite being promising, the current humanized mouse models are not uniform in their biological make-up and still in their infancies in general (Prescott and Feldmann, 2016). The same holds true for the recently published ferret model (Cross et al, 2016; Kozak et al, 2016), which also accommodates the use of wild-type isolates but suffers from being at a premature stage of development, with a lack of tools for ferrets and the more difficult holding and handling of ferrets in maximum containment. There are two commonly used EBOV nonhuman primate models, the cynomolgus and rhesus macaque, both of which do not perfectly recapitulate all but closely mimick most symptoms of human disease.…”
Section: Discussionmentioning
confidence: 74%
“…However, despite being promising, the current humanized mouse models are not uniform in their biological make-up and still in their infancies in general (Prescott and Feldmann, 2016). The same holds true for the recently published ferret model (Cross et al, 2016; Kozak et al, 2016), which also accommodates the use of wild-type isolates but suffers from being at a premature stage of development, with a lack of tools for ferrets and the more difficult holding and handling of ferrets in maximum containment. There are two commonly used EBOV nonhuman primate models, the cynomolgus and rhesus macaque, both of which do not perfectly recapitulate all but closely mimick most symptoms of human disease.…”
Section: Discussionmentioning
confidence: 74%
“…Finally, we tested the anti-BDBV efficacy of the two pan-ebolavirus bNAbs, ADI-15878 and ADI-15742, in the domestic ferret, which is the only described non-NHP model for BDBV challenge (Figures 7E and 7F) (Cross et al, 2016; Kozak et al, 2016). Animals received two doses of each bNAb.…”
Section: Resultsmentioning
confidence: 99%
“…A ferret model was recently developed that exhibits many features of filovirus disease in humans (Kozak et al, 2016). Since guinea pig studies indicated that a combination of CA45 and FVM04 is optimal for effective control of EBOV infection, we tested this cocktail in the BDBV ferret model.…”
Section: Resultsmentioning
confidence: 99%
“…All units were autoclavable and stainless steel in structure. Ferret challenge studies were performed as previously described (Kozak et al, 2016). Briefly, 6-month old male and female ferrets (Mustela putorius furo) (620–960 g) were infected by intramuscular route with 253 TCID 50 of Bundibugyo virus/H.sapiens-wt/UGA/2007 (BDBV, Genbank accession number KR063673.1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation